Assessment of the Geochemical Potential in a Complex Tectonic Environment of South-East Sicily: New Insights From Hydrochemical Data - Ristuccia, Gloria Maria; Bonfanti, Pietro; Giammanco, Salvatore; Stella, Giuseppe (Frontiers in Earth Science, 2019)
We analyzed a large dataset (143 water sampling sites, 22 variables) of chemical parameters in local groundwaters from the south-east sector of Sicily, namely the Hyblean plateau, in order to set an original evaluation of its geothermal potential using applied geochemistry. The area was affected by volcanism until about 1.4 Ma. Today, though no active volcanism occurs, it is site of surface gas manifestations of focused degassing to which a mantle source has been attributed. We identified and thence selected the most promising sites (water springs and wells) based both on their main geochemical characteristics and on their calculated equilibrium temperature (resulting in the range between 50 and 140 °C). We then applied Principal Component Analysis (PCA) to this restricted dataset and we were able to discriminate between different sources of solutes, both natural and anthropogenic. Finally, we mapped the factor scores obtained from PCA and we focused on those likely related with geothermal conditions in order to highlight the areas with the highest geothermal potential.